Mitotic chromatin marking governs the segregation of DNA damage - Juliette Ferrand; Juliette Dabin; Odile Chevallier; Matteo Kane-Charvin; Ariana Kupai; Joel Hrit; Scott B. Rothbart; Sophie E. Polo (Nature Communications)
Abstract The faithful segregation of intact genetic material and the perpetuation of chromatin states through mitotic cell divisions are pivotal for maintaining cell function and identity across cell generations. However, most exogenous mutagens generate long-lasting DNA lesions that are segregated during mitosis. How this segregation is controlled is unknown. Here, we uncover a mitotic chromatin-marking pathway that governs the segregation of UV-induced damage in human cells. Our mechanistic analyses reveal two layers of control: histone ADP-ribosylation, and the incorporation of newly synthesized histones at UV damage sites, that both prevent local mitotic phosphorylations on histone H3 serine residues. Functionally, this chromatin-marking pathway controls the segregation of UV damage in the cell progeny with consequences on daughter cell fate. We propose that this mechanism may help preserve the integrity of stem cell compartments during asymmetric cell divisions.